Peningkatan Kemampuan Berfikir Kritis Peserta Didik pada Muatan Matematika Melalui Model Pembelajaran Problem Solving di Kelas VI SDN 146/X Tanjung Solok pada Semester Ganjil Tahun Ajaran 2021/2022 - Toni Toni (Departement of Mathematics Education, 2022)
This research is motivated by the students' thinking ability in learning mathematics is still lacking. The purpose of this study was to obtain information and discuss about improving students' critical thinking skills on mathematics content through problem solving learning models in class VI SDN 146/X Tanjung Solok in the odd semester of the 2021/2022 school year. This type of research is classroom action research (CAR) by following four stages, namely planning, implementation, observation, and reflection. This research was conducted at SDN 146/X Tanjung Solok in the odd semester of the 2021/2022 academic year with the subject of class VI students totaling 17 students. This study consisted of two cycles, where each cycle consisted of two meetings. Data collection techniques used observation sheets, tests, field notes, and documentation. Data were analyzed using percentages and data reduction on students' critical thinking skills. Based on the results of research and discussion, it can be concluded that through problem solving learning models can improve students' critical thinking skills in learning mathematics in class VI SDN 146/X Tanjung Solok. This can be seen from the percentage of students' learning completeness from the first cycle (41%) and increased in the second cycle (82%).